The Effectiveness of Adaptive Learning Systems in Personalized Education - Kaitlynn Mirari (Journal of Education Review Provision, 2022)
The purpose of this in-depth literature analysis is to investigate the effect that individualized learning has on the academic performance of students. Individualized learning is a strategy to education that places the student at the center of the learning process and attempts to customize instruction to suit the specific requirements, abilities, and interests of each individual student. The review compiles and analyzes the findings of 25 separate studies that were conducted and published between the years of 2010 and 2022. These studies investigate the efficacy of individualized learning in a variety of educational settings, age groups, and subject areas. This analysis sheds light on the prospective advantages of individualized learning, as well as the difficulties and restrictions associated with putting this strategy into practice.